Integrated analysis reveals important differences in the gut and oropharyngeal microbiota between children with mild and severe hand, foot, and mouth disease - Nan Zhang; Danlei Mou; Tongzeng Li; Zhiyun Chen; Chunhua Ma; Lianchun Liang; Qiushui He (Emerging Microbes and Infections)
Little is known about alternation and difference in gut microbiota between patients with mild and severe hand, foot, and mouth disease (HFMD). We investigated the differences in gut and oropharynx microbiota between mild and severe HFMD in young children and changes in bacterial profiles as the disease progresses from acute to convalescent phase. Forty-two patients with confirmed HFMD were studied, among which 32 had severe HFMD and 10 had mild HFMD. First rectal swabs were collected from all patients at an average of 2 days (acute phase) after the onset of symptoms, and second rectal swabs were collected from 8 severe patients at day 9 (convalescent phase) after the onset. Oropharyngeal swabs were obtained from 10 patients in the acute phase and 6 in the convalescent phase. 16S rRNA sequencing was performed for all 70 samples. Compared with mild HFMD, severe HFMD exhibited significantly decreased diversity and richness of gut microbiota. Gut microbiota bacterial profiles observed in the acute and convalescent phases resembled each other but differed from those in mild cases. Additionally, 50% of patients with severe HFMD in the acute phase harboured a dominant pathobiontic bacterial genus. However, none of the patients with mild HFMD had such bacteria. Similar bacterial compositions in oropharynx microbiota were detected between mild and severe cases. Our findings indicate that severe HFMD exhibits significantly impaired diversity of gut microbiota and frequent gut and oropharyngeal inflammation-inducing bacteria. However, the results should be interpreted with caution as the number of subjects was limited.